PENANGANAN KASUS PELANGGARAN HAM BERAT DI TIMOR TIMUR DALAM PROSES PERADILAN PIDANA DI INDONESIA - Triadi Triadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The rulings regarding these three case files (with the exception of the Eurico Gutteres case) generally demonstrate that the ad hoc human rights court failed to determine who bears responsibility for the gross human rights violations in East Timor. These rulings mirror the pattern seen in three previous cases: an apparent tendency to scapegoat civilians for crimes against humanity in East Timor while shielding military personnel from accountability. The court failed to properly grasp and apply the concept of command responsibility—holding commanders or superiors accountable for events within their jurisdiction in East Timor—thereby failing to set a positive precedent for future human rights trials. These rulings pose a serious threat to the enforcement and protection of human rights in Indonesia and further indicate that the existing legal system has failed to combat crimes against humanity. Furthermore, the court failed to deliver justice to the victims of gross human rights violations in East Timor by neglecting their rights to reparation—specifically compensation, restitution, and rehabilitation—in its verdicts. These failures are also attributable to the public prosecutor's inability to effectively prove the charges and a lack of seriousness in carrying out their duties.Keywords: Violations, Gross Human Rights Violations, East Timor, Criminal Justice